1999
DOI: 10.1183/09031936.99.13357799
|View full text |Cite
|
Sign up to set email alerts
|

Lower prevalence of asthma and atopy in Turkish children living in Germany

Abstract: Lower prevalence of asthma and atopy in Turkish children living in Germany. M. Kabesch, W. Schaal, T. Nicolai, E. von Mutius. #ERS Journals Ltd 1999. ABSTRACT: Ethnic origin has been reported to affect the prevalence of atopic diseases in several studies in different parts of the world. However, little is known about the prevalence of asthma and atopy in immigrants living in Europe. The objective of this study was to evaluate the prevalence of asthma and atopy in Turkish children living in Germany and to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
2
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 25 publications
5
42
2
2
Order By: Relevance
“…The reduction of the study population by selection of children with German nationality was quantitatively negligible. In addition, ethnicity has been shown to be a significant determinant for the prevalence of atopic diseases in Germany [35].…”
Section: Discussionmentioning
confidence: 99%
“…The reduction of the study population by selection of children with German nationality was quantitatively negligible. In addition, ethnicity has been shown to be a significant determinant for the prevalence of atopic diseases in Germany [35].…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of children without German nationality was 23.1% (n=1,431) in Munich. As reported elsewhere, reporting behaviour and socioeconomic variables were profoundly different with regard to ethnic background [26]. Therefore, the analysis presented here was restricted to children with German nationality.…”
Section: Resultsmentioning
confidence: 99%
“…25 Several factors may contribute to the inconsistency in research. First, the approaches to define the outcome variable for allergies vary across the studies, including the use of serum IgE level, 24 skin prick test results, 26 and self-reported symptoms or diagnoses. 19,20 The different sensitivity and specificity across these approaches may contribute to the inconsistency, yet objective measures and doctor-diagnosed conditions have higher specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the definitions of the exposure variable for immigration status also vary. Studies defined immigrant populations with first-generation immigrants (i.e., those born outside of the host country) only, 19,23,24 a mix of first-and second-generation (i.e., those born in the host country to immigrant parents) immigrants, 20,26 or second-generation immigrants only. 25 Second-generation immigrants have been found consistently to have higher rates of allergies than first-generation immigrants.…”
Section: Discussionmentioning
confidence: 99%